An Unusual Case of Neurenteric Cyst in a Patient with Split Cord Malformation - Harris, Peter; Fleisher, Max; Liu, Matthew; Javan, Ramin; Olan, Wayne; Rosner, Michael (Journal of Neurological Surgery Reports, 2023)
Neurenteric cyst in a split cord malformation is a rare finding. We report an adult female becoming acutely symptomatic secondary to an expanding neurenteric cyst, though previous imaging had demonstrated stability. We discuss our workup and management with surgical resection and possible etiologies of her acute decline.
Keywords: neurenteric cyst; enterogenous cyst; split cord malformation; diastematomyelia; diplomyelia